2018
DOI: 10.1063/1.5012680
|View full text |Cite
|
Sign up to set email alerts
|

Cu gettering by phosphorus-doped emitters in p-type silicon: Effect on light-induced degradation

Abstract: The presence of copper (Cu) contamination is known to cause relevant light-induced degradation (Cu-LID) effects in p-type silicon. Due to its high diffusivity, Cu is generally regarded as a relatively benign impurity, which can be readily relocated during device fabrication from the wafer bulk, i.e. the region affected by Cu-LID, to the surface phosphorus-doped emitter. This contribution examines in detail the impact of gettering by industrially relevant phosphorus layers on the strength of Cu-LID effects. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…Based on the gettering experiments carried out earlier 10 and PL images shown in Fig. 2 (the first row), we confirmed that prior to RTA treatment, Cu was gettered to the phosphorus layer in all samples.…”
Section: à3supporting
confidence: 71%
See 2 more Smart Citations
“…Based on the gettering experiments carried out earlier 10 and PL images shown in Fig. 2 (the first row), we confirmed that prior to RTA treatment, Cu was gettered to the phosphorus layer in all samples.…”
Section: à3supporting
confidence: 71%
“…10. Localized contamination using a droplet allows for monitoring of the reference areas outside the contaminated region on the same wafer, which provides information about possible external contamination, e.g., during heat treatments.…”
Section: à3mentioning
confidence: 99%
See 1 more Smart Citation
“…These results provide clear evidence that Cu-LID occurs in the final cells and that PERC cell fabrication does not necessarily getter Cu from the wafer bulk. This is consistent with recent experimental results obtained with lifetime samples [22].…”
Section: Methodssupporting
confidence: 94%
“…This circumstance suggests that the absence of an increase in the removal of impurities total efficacy may mean that total efficacy depends more on crystallographic defects than on impurity concentrations. In recently published works [23,24], it was reported that impurities of metals, such as copper, form electrically active precipitates in the bulk of silicon when exposed to illumination and can cause degradation of the electrical characteristics of SC. The literature also presents data on the degradation of SC from mc-Si under illumination without explaining the reasons for this phenomenon [25].…”
Section: Dependence Of Total Efficacy On Getteringmentioning
confidence: 99%